2011
DOI: 10.1371/journal.pone.0028797
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenin Enhances Cell Migration by Regulating Stress Fiber Assembly and Focal Adhesion Dynamics

Abstract: Angiogenin (ANG) acts on both vascular endothelial cells and cancer cells, but the underlying mechanism remains elusive. In this study, we carried out a co-immunoprecipitation assay in HeLa cells and identified 14 potential ANG-interacting proteins. Among these proteins, β-actin, α-actinin 4, and non-muscle myosin heavy chain 9 are stress fiber components and involved in cytoskeleton organization and movement, which prompted us to investigate the mechanism of action of ANG in cell migration. Upon confirmation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Analysis was done similarly to already established approaches (Wei et al, 2011). A full description can be found in the supplemental experimental procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis was done similarly to already established approaches (Wei et al, 2011). A full description can be found in the supplemental experimental procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, ANG may promote degradation of the basement membrane and extracellular matrix, thus allowing endothelial cells to penetrate and migrate. In addition, our laboratory has demonstrated that cytoplasmic ANG optimizes stress fiber assembly and focal adhesion formation to accommodate cell migration by interacting with β-actin, α-actinin 4, and nonmuscle myosin heavy chain 9 [98].…”
Section: Ang Stimulates Basement Membrane Degradationmentioning
confidence: 99%
“…Metastasis is a complicated process in which distal tumor dissemination occurs after cancer cells in the primary tumor experience epithelial–mesenchymal transition (EMT) to disrupt intercellular junctions, reorganize the actin cytoskeleton, and increase cell motility for initial cancer cell spreading (Sarrió et al, 2008). Several stromal and endocrine growth factors, including insulin-like growth factor I (IGF-1), fibroblast growth factor, EGF, and angiogenin (ANG), regulate ACTN or ACTN4 binding to its cytoskeletal working partners and hence result in cell morphological changes and cytoskeletal reorganization, both of which may facilitate the metastatic process (Guvakova, Adams, & Boettiger, 2002; Shao, Wu, et al, 2010; Vandermoere et al, 2007; Wei, Gao, Du, Su, & Xu, 2011). In most breast cancers, the separation of invasive carcinoma from nearby adherent epithelium is an early step for metastases.…”
Section: The Function Of Actn4 In Breast Cancermentioning
confidence: 99%